Static recrystallization behaviour of cold rolled Mg-Zn-Y alloy and role of solute segregation in microstructure evolution. (15th July 2017) - Kim, Young Min; Mendis, Chamini; Sasaki, Taisuke; Letzig, Dietmar; Pyczak, Florian; Hono, Kazuhiro; Yi, Sangbong
Abstract: We examined the microstructure and texture evolution during the recrystallization annealing of cold rolled Mg-1Y and Mg-0.2Zn-1Y alloys. At the early annealing stage, new grains are nucleated on sub-units with 200–300 nm surrounded by dislocation walls within shear bands. The Zn and Y addition reduced the stacking fault energy which results in the high activity of non-basal deformation mechanisms and formation of segregation zones along the stacking faults. This causes the orientation of recrystallization nuclei to be effectively retained so that the texture weakens during the recrystallization without reducing the basal pole split into the sheet transverse direction. Graphical abstract: